2002
DOI: 10.1101/gr.125502
|View full text |Cite
|
Sign up to set email alerts
|

Genome Dynamics in Aging Mice

Abstract: Random spontaneous genome rearrangements are difficult to detect in vivo, especially in postmitotic tissues. Using a lacZ-plasmid reporter mouse model, we have previously presented evidence for the accumulation of large genome rearrangements in various tissues, including postmitotic tissues, during aging. These rearrangements, which were found to be organ-specific and to increase with age, have one breakpoint in the lacZ-reporter locus and the second elsewhere in the mouse genome. In this present work, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 33 publications
3
35
0
2
Order By: Relevance
“…These reporter genes are part of a lambda or plasmid construct that can be recovered from genomic DNA and tested in E. coli for mutational inactivation of the reporter gene. Since then, a plethora of data has been published on somatic mutation frequencies and spectra in these animals, both induced mutations after exposure to a variety of mutagenic agents and spontaneous mutations accumulating during the normal aging process[5153]. Using transgenic reporter genes, it has been shown that mutation frequencies in most tissues, especially actively proliferating tissues, such as the epithelia in the small intestine, consistently show an age-dependent increase (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…These reporter genes are part of a lambda or plasmid construct that can be recovered from genomic DNA and tested in E. coli for mutational inactivation of the reporter gene. Since then, a plethora of data has been published on somatic mutation frequencies and spectra in these animals, both induced mutations after exposure to a variety of mutagenic agents and spontaneous mutations accumulating during the normal aging process[5153]. Using transgenic reporter genes, it has been shown that mutation frequencies in most tissues, especially actively proliferating tissues, such as the epithelia in the small intestine, consistently show an age-dependent increase (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Since the occurrence of somatic copy number changes has been shown to increase with age in sev- eral tissues in mice (Dolle and Vijg 2002) and also in peripheral blood in cancer-free humans (Forsberg et al 2012;Jacobs et al 2012;Laurie et al 2012), we assumed that single nucleotide somatic mutations might also increase with age. Therefore, we chose a healthy person of extreme age as our subject, anticipating that during a long lifetime, mutations leading to the fittest HSCs might lead to clonal selection and thus the detectability of somatic mutations (Naylor et al 2005;Gibson et al 2009).…”
mentioning
confidence: 99%
“…Our own data obtained with the lacZ transgenic reporter mice, extensively cited by de Grey, indicate surprisingly high numbers of genome rearrangement mutations in organs such as liver and heart (Dollé et al, 2002). In our model genome rearrangements occur as a consequence of a breakpoint in a lacZ reporter gene and a second breakpoint elsewhere in the mouse genome, either on the same chromosome (in which case the event reflects a deletion or inversion) or on another chromosome (resulting in a translocation).…”
mentioning
confidence: 68%